Effectiveness of mechanically tenderized beef labels on influencing practices of cooking beef in British Columbia - Heran, Arunjit; BCIT School of Health Sciences, Environmental Health; Sidhu, Bobby (BCIT Environmental Public Health Journal, 2015)
Background: Mechanically tenderized beef poses a higher risk for Escherichia coli 0157:H7 infection than intact beef and has been implicated in several outbreaks. As such, all products are mandated to be labeled in Canada. Purpose: This study assessed the effectiveness of mechanically tenderized beef labels on influencing practices of cooking beef in British Columbia. Methods: 74 adults within British Columbia who cooked beef were surveyed electronically using a snowball method. An inferential (Pearson chi-square analysis) and descriptive analysis was performed on the nominal data in PSPP and Microsoft Excel respectively. Results: Only 8% of respondents abided with information on mechanically tenderized beef labels. No statistically significant associations were found between practices of abiding with information on mechanically tenderized beef labels and various socio-demographic factors (e.g. age, gender, education level, and food safety education) (p<0.01). The practice of not using food thermometers was the major contributing factor that lowered the effectiveness of mechanically tenderized beef labels. Conclusion: Mechanically tenderized beef labels were ineffective in influencing behaviours of cooking beef in British Columbia. Therefore, other risk communication strategies are needed to persuade adults in British Columbia to adequately cook mechanically tenderized beef products. Recommendations: Future studies can assess whether the general public is properly cooling mechanically tenderized beef as the label does not address this practice.